Evaluation of the relationship between autistic spectrum disorders with Lyme disease - (:unkn) unknown (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2018)
Objective: Autistic spectrum disorders (ASD) are chronic neurodevelopmental disorders leading to deterioration in social, communicative and behavioral skills. Etiology and pathogenesis of the disease has not been elucidated fully yet. In this study, the aim is to investigate the relationship between the Lyme disease with ASD. Methods: Forty children, aged between 3 and 18 years and their mothers participated as the study group and the patients' 18 healthy brothers participated as the control group in this study. The groups compared clinical and serological for Lyme disease. Autism severity was assessed by Childhood Autism Rating Scale (CARS). Serological evaluations was applied with EnzymeLinked ImmunoSorbent Assay (ELISA) and Western Blot (WB) tests. Results: All participants' serums was analyzed by ELISA for Borrelia burgdorferi antibodies and WB test was applied to serums with positive and border levels. WB IgM antibody levels were determined negative for all four patients and one healthy control. WB lgG test performed in two patients, the result was found negative for one of them and one was border. The WB IgM test was made for one mother and it was found negative, WB lgG test was performed for six mothers and the results were found negative for four (66.7%) of them and two (33.3%) were border. No statistically significant difference was found between WB test results which applied for patients and control group. Discussion: Although tick-borne infections are common in Turkey, studies investigating the relation-ship between autism and Lyme disease have been limited. This study is one of the studies investigating the relationship between the Lyme disease with ASD. In our study the ASD patients, their mothers and healthy brothers as the control group was evaluated and Lyme disease was not detected in any participants serological and clinical.
Keywords: autistic spectrum disorders; Lyme disease; child; adolescent; ANTIBIOTIC-THERAPY; FETAL-BRAIN; CHILDREN; AUTOANTIBODIES; MARKERS